2000
DOI: 10.1002/0471141755.ph0702s08
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Intestinal Mucosal Permeation of Compounds Using Caco‐2 Cell Monolayers

Abstract: Step-by-step protocols are provided in this unit for the measurement of apparent permeability coefficients of compounds using Caco-2 cell monolayers as an in vitro model of the intestinal mucosa. Procedures for culturing the cells and transmonolayer transport studies are also included. Critical issues for successfully estimating intestinal mucosal permeation of drugs are discussed. Step-by-step protocols are provided in this unit for the measurement of apparent permeability coefficients of compounds using.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…The Papp values of propranolol and atenolol tested in the Caco-2 cell monolayers were 2.54 x 10 -5 cm/s and 3.35 x 10 -7 cm/s, respectively, as determined by HPLC (Figure 3) and were comparable to the results reported in literature (Chong et al, 1997;Yee, 1997;Walle et al, 1999;Gao et al, 2001). Our results indicated that the Caco-2 model could be used to evaluate the transport of cinnamon extract.…”
Section: Stability Of the Reaction Systemsupporting
confidence: 89%
“…The Papp values of propranolol and atenolol tested in the Caco-2 cell monolayers were 2.54 x 10 -5 cm/s and 3.35 x 10 -7 cm/s, respectively, as determined by HPLC (Figure 3) and were comparable to the results reported in literature (Chong et al, 1997;Yee, 1997;Walle et al, 1999;Gao et al, 2001). Our results indicated that the Caco-2 model could be used to evaluate the transport of cinnamon extract.…”
Section: Stability Of the Reaction Systemsupporting
confidence: 89%
“…Bidirectional transport of [ 14 C]erythromycin across MDCK-MDR1 was carried out as described previously (Gao et al, 2000), with some modifications. The purpose of the transport experiment was to determine that erythromycin was a good substrate for P-gp with a good efflux potential which could be used to test the functionality of P-gp in rabbit corneas.…”
Section: Methodsmentioning
confidence: 99%
“…Bidirectional transport experiments were performed as previously described 20 with some modifications. All experiments were done at 378C with constant mixing in a shaking water bath (60 rpm).…”
Section: Transport Experimentsmentioning
confidence: 99%
“…1 filter inserts (six-well) and maintained in high-glucose Dulbecco's modified Eagle medium supplemented with 10% fetal bovine serum, 0.1 mM nonessential amino acids, 2 mM L-glutamine solution, 100 U/mL penicillin, and 100 mg/mL streptomycin as described previously. 20 Experiments were conducted on these cells after 6 days of culture. The functional expression of P-gp transporter in the transfected cells was checked using Western blotting techniques and […”
Section: Introductionmentioning
confidence: 99%